ANALISIS DAN PERANCANGAN TEKNOLOGI FRAME RELAY DENGAN MENGGUNAKAN ENCHANCED INTERIOR GATEWAY ROUTING PROTOCOL (EIGRP): STUDI KASUS PADA PT.XYZ - Fuad Mumtaz (Institut Bisnis dan Informatika Kwik Kian Gie, 2015)
The purpose of this research was to determine and design the Wide Area Network (WAN) at PT. XYZ. The method used is the method of analysis that includes field surveys, interviews with administrators, library research, design and simulation, and evaluation. The design and simulation of the network used is Dynamips and OPNET Network Simulator. Based on the comparison of WAN technology and the needs of users is obtained that the Frame Relay technology suitable for connecting headquarters with branch offices in PT. XYZ. Based on simulation of routing protocol comparison has been done it can result EIGRP smallest impact on Frame Relay in terms of bandwidth usage, summarization would reduce the size of routing updates and load balancing to set the path, so that the data transmission time of data transmission becomes more efficient. The conclusions that can be drawn from the results of the evaluation is, the use of Frame Relay and Routing Protocol EIGRP allows network in PT. XYZ to evolve and adapt according to the needs